Cytotoxicity and bioadhesive properties of poly-N-isopropylacrylamide hydrogel. Issue 4 (April 2019) - Capella, Virginia; Rivero, Rebeca E.; Liaudat, Ana C.; Ibarra, Luis E.; Roma, Dardo A.; Alustiza, Fabrisio; Mañas, Fernando; Barbero, César A.; Bosch, Pablo; Rivarola, Claudia R.; Rodriguez, Nancy
Abstract: Several hydrogel surfaces present properties that simulate the mechanical and physicochemical features of extracellular matrix (ECM), providing a platform that mimic the native cellular milieus. Poly- N -isopropylacrylamide (PNIPAM) hydrogels are receiving attention in biomedical field due to their thermosensibility and soft texture. However, more extensive biocompatibility and cellular interactions studies with cell lines are needed. Therefore, the aim of this study is focus on evaluating the biocompatibility of PNIPAM through cytotoxicity, genotoxicity, and proliferation tests in murine preadipose cells (3T3-L1), human embryonic kidney cells (HEK293) and human carcinoma-derived cells (A549) in presence of hydrogel surfaces. Bioadhesive capacity above PNIPAM surfaces was also analyzed. MTT and neutral red uptake assays shown non-cytotoxic effect of PNIPAM in the studied cell lines. Genotoxicity was evaluated by the single-cell gel electrophoresis assay, where DNA damages were not detected. [ 3 H]-thymidine staining allowed to corroborate that cell proliferation had progressed correctly. Adopted morphologies for each cell line over PNIPAM were similar to cell growing observed on polystyrene, indicating that the surfaces favor the cell attachment during 5 days' culture. The good biocompatibility of PNIPAM surfaces make it an interesting scaffold with clinical potential in tissue regeneration engineering, and a possible adipose and kidney tissue-engineered construct.